Improved ionic solid/viologen hybrid electrochromic device using pre‐bleached Prussian‐blue electrode. Issue 4 (25th March 2021) - Chaudhary, Anjali; Pathak, Devesh K.; Tanwar, Manushree; Kandpal, Suchita; Ghosh, Tanushree; Rani, Chanchal; Kumar, Rajesh
Abstract: The authors demonstrate how a simple step of loading an electrochromically active Prussian blue (PB; an ionic solid) electrode with Li + ions can help in achieving a more efficient viologen based solid state hybrid electrochromic device. To accomplish this, two different devices, with and without Li + ion loaded PB electrodes, have been fabricated. These devices have been compared in terms of their current‐voltage response, bias dependent optical modulation and corresponding colour switching to establish the role of Li + ion in charge transport and charge balancing involved during bias induced redox mediated colour switching of the two devices. The Li + containing PB electrode device exhibits a superior performance with twice (40%) the value of colour contrast (20%), quick response switching (1.3 s), excellent stability (8400 s) and better power efficiency as compared to the device containing as‐synthesised PB electrode. A mechanism has been proposed to explain the role of the Li + ion which is later substantiated using bias‐dependent in situ Raman spectroscopic evidences.